DESIGN AND ANALYSIS OF BUOYANCY ENGINE SYSTEMS ON CHANGES IN BUOYANCY FORCES IN UNDERWATER GLIDER - Finali, Asmar; Eka Darma, Yeddid Yonatan; Hanafi, Agung Fauzi (Universitas Muhammadiyah Metro, 2023)
The vast and deep conditions of the ocean still contain many objects that have not been explored. Based on the type of autonomous underwater vehicle (AUV) device design, it consists of types that can drift, glide, and can propel itself in water. Types of AUV without propellers (nonpropelled, drifter). or glider), can float without thrusters or glide up and down the water by changing its buoyancy. This AUV uses little or no battery power compared to propeller-driven AUVs, but cannot perform as many maneuvers. Variable Buoyancy System used in different types of underwater craft, designed and built for specific rides and applications. Therefore, each system is completely different from the others. This research focuses on systems that raise and lower volume, using components such as diaphragms, bladders, and bellows. It is possible to use a diaphragm for a buoyancy engine to make the vehicle easier to fabricate. The aim of this research is to determine the magnitude of deformation of the diaphragm made from silicon rubber and EPDM (ethylene propylene diene monomer) with varying thickness of 0.5 mm; 1mm and 2mm. Through the Finite Element Method approach to obtain deformation analysis modeling, EPDM material provides higher deformation than using silicon material. However, for pressures of no more than 0.5 bar, using a rubber thickness of 0.5 mm is not suitable. So the appropriate application for Gliders is 1 mm thick.